Study on Esculetin to reduce cardiotoxicity induced by Doxorubicin - Li, Xiao; Yu, Xiaolei; Xu, Fan; Li, Qingshan; Xu, Xiao (Nepalese Journal of Cancer, 2021)
Objective: To investigate the protective effects and mechanisms of esculetin(Esc) on H9C2 cells injury induced by doxorubicin (DOX). Methods: H9C2 cells were cultured and divided into control group, model (DOX) group and intervention (ESC + DOX) group. Flow cytometry was used to detect apoptosis of H9C2 cells and reactive oxygen (ROS) level in H9C2 cells; Western blotting to detect the cleaved Caspase-3, cleaved PARP, bid and Bcl-2 protein expression in H9C2 cells. Results: The number of apoptosis and ROS level of H9C2 cells in the model group, the expression of cleaved Caspase-3, cleaved PARP and Bid protein in the model group were obviously higher than control group; and the Bcl-2 protein expression was obviously lower (P < 0.05).The number of apoptosis and ROS level, cleaved Caspase-3, cleaved PARP and Bid protein expression in H9C2 cells in intervention group were obviously lower than model group;the Bcl-2 protein expression was obviously higher (P< 0.05). Conclusion: Esculetin can reduce the cardiotoxicity induced by doxorubicin by reducing apoptosis and ROS level.